EXPERIMENTAL EVIDENCE ON PHLOGOPITIC MANTLE METASOMATISM INDUCED BY PHENGITE DEHYDRATION - Wunder B.; Melzer S. (My University, 2003)
To simulate metasomatism at convergent plate boundaries, the process of phengite dehydration, followed by reactions between the expelled fluid and a model mantle material consisting of forsterite + enstatite, was investigated at subduction zone conditions using a piston cylinder apparatus. An experimental technique has been devised in which the fluid, which should be set free during phengite decomposition at about 950°C and 3.5 GPa, would be triggered by a temperature gradient of about 50 K to infiltrate through a perforated Au-foil the hotter part of the capsule, containing the model mantle material. Crystallization of phlogopitic mica and Al-rich enstatite at the boundary phengite – (forsterite + enstatite), representing the „slab – mantle“ contact region, indicates successful experimental simulation of mantle wedge metasomatism. Cs-Rb exchange coefficients KD, determined from compositions of newly formed phlogopitic micas, recrystallized phengite and of an amorphous phase, representing the quenched liquid, agree well with recently determined alkali-fractionation data between micas and fluid. The composition of the quenched liquid is rich in alkali, aluminium, silicon, and poor in magnesium, which is in agreement with fluid solubility data determined in earlier experimental studies at similar conditions.